Perspektif Komunikasi Islam Dalam Menyikapi Kekerasan Verbal Pada Vlog Game Brandonkent Everything - Ilham Wijaya; Achmad Syarifudin; Manalullaili Manalullaili (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research is entitled "Perspectives on Islamic Communication in Responding to Verbal Violence in BrandonKent Everything's Vlog Game". In this study, the authors raise the issue of how the perspective of Islamic communication responds to verbal violence in the BrandonKent Everything vlog game. The background of this research is the presence of verbal violence in BrandonKent's game vlog shows. The purpose of this study was to find out the perspective of Islamic communication in responding to verbal violence in the BrandonKent Everything game vlog. The theory used in this study is the Hypodermic Needle Theory. The type of research used in this study is a qualitative research method that produces descriptive data. The source of the data obtained in this study is directly from the game's vlog broadcast on the BrandonKent Everything YouTube channel. The results of this study indicate that there is violence in vlog game shows on the BrandonKent Everything channel, namely words that contain verbal violence such as swearing, insulting, cursing, mocking and cornering in a loud tone and as if yelling. This verbal abuse can be found in the video games he plays on BrandonKent Everything's YouTube channel.